SYNERGISTIC EFFECT OF QUERCETIN AND EPIGALLOCATECHIN-3-GALLATE AS AGENTS TO PREVENT CONNECTIVE TISSUE DISINTEGRATION IN THE PERIODONTIUM OF RATS UNDER SYSTEMIC AND LOCAL ADMINISTRATION OF LIPOPOLISACCHARIDE OF SALMONELLA TYPHI - A.M. Yelins’ka; V.O. Kostenko (Проблеми екології та медицини)
The aim of the present study was to investigate the co-effect produced by water-soluble form of quercetin and epigallocatechin-3-gallate (EGCG) on biochemical markers of periodontal organic matrix depolimerization under systemic administration and local application of S. typhi lipopolisaccharide (LPS). The studies were conducted on 30 white rats of the Wistar line weighing 180-220 g, divided into 5 groups: the 1st included intact animals, the 2nd was made up of animals after the combined systemic and local LPS administration, the 3rd and 4th groups included animals, which were being given injections with water-soluble form of quercetin (10 mg / kg) and EGCG (21.1 mg / kg) respectively 3 times a week, starting on the 30th day of the systemic LPS administration, and the 5th group involved rats, which were injected with co-administered water-soluble form of quercetin and EGCG. It has been found out that the co-effect produced by quercetin and EGCG under systemic and local LPS administration is accompanied with reduced concentration of N-acetylneuraminic acid (NANA) by 31.8 and 32.8% respectively in the soft periodontal tissues compared with values for the animals received separate quercetin and EGCG during the experiment. However, no differences have been detected between the groups exposed to combined or separate action of the above mentioned agents in the experiment when assessing free hydroxyproline (FHP) and glycosaminoglycans (GAGs) content in the soft tissues of periodontium. At the same time combined use of quercetin and EGCG under experimental conditions led to the decrease in the FHP content in the alveolar bone by 24.5 and 20.2% respectively compared with values for the animals received separate quercetin and EGCG. NANA concentration was reduced by 35.0 and 41.3% respectively. Thus, the co-administration of water-soluble form of quercetin and epigallocatechin-3-gallate under systemic and local introducing of S. typhi lipopolysaccharide has been proven to be more effective means for preventing and correcting periodontal connective tissue disruption than this occurs at separate administration of each of the polyphenols.